MATRONA DE ÉFESO AND MARIA MUTEMA: RECREATION OF A NARRATIVE OF THE SATYRICON, BY PETRÔNIO, PRESENT IN GRANDE SERTÃO: VEREDAS, BY GUIMARÃES ROSA - Oliveira, Nicolas Pelicioni de [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
I present in this article some of the literary narrative procedures adopted by Joao Guimaraes Rosa in the composition of his short stories, and, mainly, a comparative analysis between The Case of Maria Mutema and Father Ponte, a tale inserted in The Devil to Pay in the Backlands (Grande Sertao: Veredas), and the widow of Ephesus, a tale inserted in The Satyrica, by Petronius. With a comparative analysis I try to understand as parodical the procedure by which the values of Classical Antiquity were interpreted according to the rules of Brazilian Northern Sertao from the beginning of the 20th century, as the result of this parody seems to subvert the ethical values of Rome until their completely inversion.
Keywords: Maria Mutema; Satyrica; The Devil to Pay in the Backlands; widow of Ephesus